2018
DOI: 10.3382/ps/pey252
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime productivity of conventionally and precision-fed broiler breeders

Abstract: A precision feeding (PF) system was developed to increase broiler breeder lifetime reproductive performance through improved flock uniformity. The current study consisted of 2 rearing and 3 laying treatments. From 0 to 22 wk of age, 480 Cobb male grandparent line pullets and 80 Cobb MX males were fed once daily as a group (CON), or individually with a PF system. Pullets were housed in 6 replicate pens of 40 birds, and cockerels in one pen per treatment. During lay, CON and PF treatments continued, and a third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 26 publications
2
47
0
3
Order By: Relevance
“…Meal:visit ratio was much lower (around 20% for all treatments) in the rearing phase compared with the laying phase (around 80%) for those treatments that commenced egg production earlier (8L:16D and high BW treatment; Figure 8 ). The meal:visit ratio was in line with results from Zuidhof (2018) who looked at Cobb grandparent pullets and found an average meal:visit ratio of 17% between week 2 and 22. However, the meal:visit ratio of the 12L:12D standard BW treatment stayed around 30% in the laying phase, indicating these birds were hungrier compared with those treatments that had commenced egg production.…”
Section: Resultssupporting
confidence: 86%
“…Meal:visit ratio was much lower (around 20% for all treatments) in the rearing phase compared with the laying phase (around 80%) for those treatments that commenced egg production earlier (8L:16D and high BW treatment; Figure 8 ). The meal:visit ratio was in line with results from Zuidhof (2018) who looked at Cobb grandparent pullets and found an average meal:visit ratio of 17% between week 2 and 22. However, the meal:visit ratio of the 12L:12D standard BW treatment stayed around 30% in the laying phase, indicating these birds were hungrier compared with those treatments that had commenced egg production.…”
Section: Resultssupporting
confidence: 86%
“…We argued that growth heterogeneity is maintained by feed restriction rather than caused by it. While the recent studies employing precision feeding systems have achieved extremely uniform flocks, they also highlight an enormous variation in attempts to access feed in these experiments which points towards large individual differences in feeding motivation (Zuidhof, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The exact eating pattern allowed by the precision feeding system is a combination of competition for entry into the cubicle and limitations imposed on eating time by the experimenters. Because early trials allowing for longer eating times (up to 10 min) showed that feed intake rates decrease logarithmically over time, subsequent experiments have used a maximal meal time of 1 min (Girard et al, 2017a;Zuidhof et al, 2017;Zuidhof, 2018). With this setup, precision-fed birds eat approximately 8-10 meals per day with an average meal size of around 8-10 g, although the total number of visits to the feeder was much higher and averaged 51 visits (full range: 28-138 visits) per day and bird (Girard et al, 2017a;Zuidhof et al, 2017;Zuidhof, 2018).…”
Section: Improving the Breeder Situation: Breeding Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of poultry, precision feeding stations in broiler breeders can provide individual information about their performance in terms of growth rate and feed intake during rearing and lay (Hadinia et al, 2019). This information allows individual and automatic management of the feed restriction level and improve body weight uniformity in the flock (Zuidhof, 2018). For breeding selection purposes, individual performance records with precision feeding enable selection for feed efficiency.…”
Section: Individual Feed Intake Recording Systemsmentioning
confidence: 99%